Jurisprudence du travail - Gagné, Jean-H. (Relations industrielles / Industrial Relations, 1951)
SummaryUnder this heading, which witt appear in every issue of the Industrial Relations Review, we shall present the principal points of interest encountered in the arbitration awards rendered by the councils of arbitration during the three months preceding the publication of each of the issues of this review.Occasionally, we shall analyze also, under this heading, the judgments rendered by the Courts of Common Law during the same period and relevant to labour laws. The arbitration awards studied in the present issue are those rendered during the months of May, June and July, 1951. We are only reporting the awards which contain points of particular interest to our readers.